Uncovering Listeria monocytogenes hypervirulence by harnessing its biodiversity - Maury, Mylène M. (Nat Genet, 2016)
Microbial pathogenesis studies are typically performed with reference strains, thereby overlooking microbial intra-species virulence heterogeneity. Here we integrated human epidemiological and clinical data with bacterial population genomics to harness the biodiversity of the model foodborne pathogen Listeria monocytogenes and decipher the basis of its neural and placental tropisms. Taking advantage of the clonal structure of this bacterial species, we identify clones epidemiologically associated with either food or human central nervous system (CNS) and maternal-neonatal (MN) listeriosis. The latter are also most prevalent in patients without immunosuppressive comorbidities. Strikingly, CNS and MN clones are hypervirulent in a humanized mouse model of listeriosis. By integrating epidemiological data and comparative genomics, we uncovered multiple novel putative virulence factors and demonstrated experimentally the contribution of the first gene cluster mediating Listeria monocytogenes neural and placental tropisms. This study illustrates the exceptional power of harnessing microbial biodiversity to identify clinically relevant microbial virulence attributes.